Entrepreneurs' Well-Being: A Bibliometric Review - Sánchez-García, José Carlos; Vargas-Morúa, Gioconda; Hernández-Sánchez, Brizeida Raquel (Frontiers in Psychology, 2018)
The present article aims to summarize and classify existing research entrepreneurs' well-being through a bibliometric literature review. Its main objectives are: to identify the different theoretical perspectives and research strands that characterize and define literature on entrepreneurs' well-being and highlight the connections between them; as well to look for emerging trends and gaps in its literature by comparing the most recent works with those that represent the field's core. The document is based on bibliometric data: it uses citation techniques to select, analyze, and interpret citation patterns within the literature on entrepreneurs' well-being. The paper identifies six main groups, as well as several specific research flows and common themes that represent academic publications on entrepreneurs' well-being. The research strands on the topic are grouped into six different theoretical perspectives grounded in entrepreneurship related to: culture, education, innovation, sustainable development and small business; psychological well-being; social entrepreneurship and economic development; women and employment; and self-employment; life satisfaction and economic growth, and business administration. Data from the most recent publications were used to verify whether original topics and themes are reflected in contemporary debate and in which fashion. Limitations related to search engines, such as missing keywords were accounted by utilizing three different database as well as expanding keyword number. From a practical perspective, this research is expected to contribute on theory construction, management decision making, and teaching. This study describes the growing development of the literature on entrepreneurs' well-being, and the underlying structure of the different streams of research therein.